An Analytical Study Of Monetary Stability In Syria During The Period(1990-2016) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of this research is to study the monetary stability in Syria represented by inflation and the interest rate internally and the exchange rate at the external level, as monetary stability is one of the most important goals on which countries depend to ensure the continuity of economic activity, according to scientific foundations where it extrapolates factors of monetary stability and the factor of monetary stability During the period (1990-2016), the research proceeded from the hypothesis that Syria suffers from monetary instability throughout the period studied. The research reached the conclusion that Syria suffered during the study period from a large imbalance in monetary stability, especially after the war on Syria, and the existence of a large imbalance between the nominal and real interest rate caused by the president, the rise in inflation rates, in addition to the growth of domestic liquidity simultaneously with the decrease of GDP.